Reiterative reflection in the library instruction classroom. Issue 3 (1st August 2019) - Whitver, Sara Maurice; Riesen, Karleigh Knorr
Abstract : Purpose: This study aims to explore the application of reflective pedagogy within a course-embedded library instruction session (as opposed to a semester-long credit bearing course) as a means to foster transfer learning of research practices. Design/methodology/approach: This conceptual essay adapts theories of reflection for transfer learning as found in composition and rhetoric literature to the traditional course-embedded library instruction classroom. Findings: The application of reflection as a structured learning construct may have the potential to transform the library instruction classroom into an environment where transfer learning is more likely to take place. Research limitations/implications: Most models for transfer learning are based on semester-long courses and do not take into account the abbreviated context of the traditional library instruction event. This presents a challenge to any adaptation of theory, as library instruction is often an event isolated to one or a few sessions. Practical implications: This study provides a structure for reflective pedagogy for librarians who desire to engage students in practices that offer the potential of fostering transfer learning. Originality/value: Librarians are practicing reflective pedagogies in semester-long information literacy courses, but few have used reflection in traditional instruction sessions beyond the documentation of student learning for assessment purposes. This essay provides a theory that extends reflective pedagogies into the traditional library instruction classroom with the hope of fostering transfer learning.